Reactive Collisional Spectroscopy: Scalar and Vector Information From Numerically Intensive Computing. Issue 3 (1991) - Laganà, Antonio; Gervasi, Osvaldo; Alvariño, José M.
Abstract : Advances in computer technologies have made it possible to extend the numerical investigation of the detailed structure of reactive properties to several atom–diatom systems. This has allowed a better understanding of the energy structure of the reaction intermediate and of the role it plays when reaction occurs.